Functional roles of immune cells in osteoporosis - Qi, Zhenqian; Luo, Jiayi; Xiao, Zheng; Yang, Dazhi (Frontiers in Immunology, 2025)
Osteoporosis is a systemic skeletal disorder characterized by reduced bone mass and deterioration of the bone microarchitecture, resulting in an increased risk of fragility fractures. Emerging evidence underscores the crucial role of immune cells as central regulators of bone metabolism. Various immune cells, including T lymphocytes and their subsets, such as TH1, TH2, TH17, and Treg cells, as well as B lymphocytes, macrophages, dendritic cells, neutrophils, mast cells, and eosinophils, orchestrate bone remodeling through complex mechanisms. These mechanisms include direct and indirect regulation of osteoclast differentiation and osteoblast function, often mediated by cytokine networks. For example, T-cell subsets exert diverse and sometimes opposing effects, whereas B cells modulate the RANKL/OPG axis. Macrophages exhibit a biphasic role, with pro-inflammatory M1 and anti-inflammatory M2 phenotypes differentially influencing bone homeostasis. This review synthesizes current knowledge on the functional contributions of immune cells to osteoporosis pathogenesis, highlighting their therapeutic potential for innovative treatment strategies.